(untitled) - Guilherme Fleury Perini; Paulo Vidal Campregher; Fabio Pires de Souza Santos; Nelson Hamerschlak (Arquivos de Neuro-Psiquiatria)
Primary central nervous system lymphoma is a rare disease, with bad prognosis. Neurologists and neurosurgeons should be familiar with the diagnostic,and biologic features, as well as the initial management of patients. A correct approach to these patients is mandatory for a better outcome.